Indikator Sistem Demokrasi Berbasis Konsep Otonomi Daerah Di Tinjau Dari Undang-Undang Nomor 23 Tahun 2014 Tentang Pemerintahan Daerah - Muhammad Irpan; Ernawati Suwarno (Journal of Innovative and Creativity, 2026)
The Implementation of a Democracy Indicator System Based on Concept of Regional Autonomy, Since The reformation in 1998, give a great hope for occurrence change all aspects of national and state life. That are politics, economics, and law. One of pillars democracy is concept of division power known by montesquieu in his theory of triaspolitica which divides nation power into three nation political powers (executive, judicial and legislative). Democracy is a foundation and mechanism for application power based on the principle of equation and human equality, which places human as owner of sovereignty which known as the principle of people sovereignty. Regional autonomy is authority of autonomous regions to regulate and manage the interests of local society according to their own initiatives based on society’s aspirations in accordance with legislation regulations. Article number 1 of Regulations Number 23 of 2014 about Regional Government mention that decentralization is the handover of government authority by the government to autonomous regions based on the principle of autonomy. Indonesia is a unitary state form of Republic as mention in Article 1 number (1) of the Constitution 1945. Following up on these provisions, Article 18 of the Constitution 1945 confirms that the Unitary State of the Republic Indonesia is divided into Provincial Regions and Provincial Regions divided into Regencies and Cities each Province, Regency and City has Regional Government that is regulated by Law, So in the context of the Unitary State, relationship of authority between the central and the regions in Indonesia is based on three patterns, namely decentralization, deconcentration, and co-administration (medebewind). Regional Government It can be said to be democratic if in a democratic system, authority and power are built and maintained based on the agreement of the citizen. While in an undemocratic system the citizen’s agreement is not part of the requirements. The concept of regional autonomy reflects the democratic value because it has fulfilled the spirit of democracy in the society in purpose of construction by taking agreements between the local society and the government from the lowest level, that is village / village office, sub-district to Regency / City.